INDIRECT SPEECH ACTS IN TOBA DREAM MOVIE - Taufan Fadilah; Isli Iriani Indiah Pane (LINGUISTICA, 2019)
This study focused on indirect speech act used by the main characters in Toba Dream movie. The objectives of the study were to: (1) find out the types of indirect speech acts used in Toba Dream movie, and (2) describe how types of indirect speech acts used in Toba Dream movie. This research was conducted by using descriptive qualitative method. The data of the study were all utterances uttered by the main character in Toba Dream movie and collected by watching the movie.  The result of the study showed that there were four types of indirect speech acts found in Toba Dream movie, they were: representative, directive, commisive, expressive containing indirect speech acts in Toba dream Movie. Representative (25,71%) were realized by interrogative sentences and imperative sentences. Directive (21,43%) were realized by declarative sentences and interrogative sentences. Commisive (14,28%) were realized by declarative sentences. The main characters in Toba dream movie dominated the use of indirect speech act to express statement, command and warning. It showed that they could produce the language more politely and keep the hearer’s face while getting instruction or information indirectly.Keywords: indirect speech act, movie pragmatic, Toba Dream